2004
DOI: 10.1111/j.1398-9995.2004.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to house dust endotoxin and allergic sensitization in adults

Abstract: Our results indicate that current exposure to higher levels of house dust endotoxin might be associated with a decreased odds of allergic sensitization in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 37 publications
5
19
0
Order By: Relevance
“…Stronger effects for higher cut-offs for sensitisation are in agreement with previous findings [2,25]. Associations between living-room floor dust endotoxin and sensitisation as shown by GEHRING et al [2] were not found in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…Stronger effects for higher cut-offs for sensitisation are in agreement with previous findings [2,25]. Associations between living-room floor dust endotoxin and sensitisation as shown by GEHRING et al [2] were not found in the present study.…”
Section: Discussionsupporting
confidence: 79%
“…The analysis of the correlations between the investigated factors showed a significant (p < 0.05) positive correlation of the concentrations of all allergens determined in the settled dust (Der p1, Fel d1, Can f1 and Bla g1) expressed in ng or U per 1 m 2 of the floor with the concentrations of this dust. Besides, significant positive correlations were shown between the concentrations of Der p1, Fel d1 and Can f1 In comparison with other studies, we found that the mean concentration of endotoxins in Polish houses was similar to those obtained in Germany [24] and Croatia [25]. The mean levels of endotoxins found in the USA and in Germany were slightly higher than ours [26][27][28][29][30].…”
Section: Analysis Of (1→3)-β-d-glucansmentioning
confidence: 33%
“…Although it has been argued that especially microbial exposure in early childhood contributes to the reduction of allergic sensitisation [1,5], there are studies suggesting that exposure during adulthood continues to protect against atopy. GEHRING et al [12] found an association between elevated house-dust endotoxin levels and a decreased prevalence of allergic sensitisation in adults. In addition, two studies in farmers found inverse relationships between airborne endotoxin exposure and atopic asthma [13] and atopy [14].…”
mentioning
confidence: 99%